2007
DOI: 10.1080/10790268.2007.11753970
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Traumatic Spinal Cord Injury With Onset During Adolescence: A Qualitative Study

Abstract: Background/Objective: Spinal cord injury (SCI) occurring during adolescence poses additional challenges because of the concurrent age-specific bio-psychosocial development. Full understanding of the psychosocial dimensions of rehabilitation requires exploration of the patient perspective. The objective of this study was to focus on psychosocial factors from the patient perspective in persons who had previously sustained a SCI during early and mid-adolescence (11-15 years of age). Methods: Twenty-four of the 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The key function of role models in the rehabilitation of patients with SCI, both in promoting an active lifestyle and in helping to establish a new identity, has been proposed previously. 13,[24][25][26] However, the evidence that does exist is mostly anecdotal and future evaluation, and research in this field is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key function of role models in the rehabilitation of patients with SCI, both in promoting an active lifestyle and in helping to establish a new identity, has been proposed previously. 13,[24][25][26] However, the evidence that does exist is mostly anecdotal and future evaluation, and research in this field is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the individuals were interviewed about the psychosocial factors that had promoted their readjustment during the first year after injury. 13 The hypothesis is that their spontaneous comments about coping with SCI can be categorized into strategies of coping similar to those identified in previous studies of coping with SCI.…”
Section: Introductionmentioning
confidence: 92%
“…For adolescents, feeling accepted by peers and being able to discuss issues such as sexuality, dating, driving and college with other teens with SCI is important for their developmental growth. 15,16 This might explain why caregivers of adolescents compared to caregivers of younger children were more likely to view interactions with others with disabilities as important during rehabilitation. In addition, meeting adults with disabilities was also mentioned as a promoting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal data are needed to examine how outcomes change over time. Related to this, parent-report data were used for outcomes of the youngest children (ages [2][3][4][5]. Past research has demonstrated that parent-report may be more a function of the parent's mental health than the child's mental health 17 ; regardless of this, self-report data were not feasible for these youngest children.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to dealing with the usual challenges that come with being a young person in today's society, they face the challenges involved with acquiring a new disability, which may include physical, social, and emotional issues and adaptations. 1,2 Although acquiring a disability should not be seen as inherently detrimental to positive psychological functioning, it is important to acknowledge that facing such an experience during a vulnerable developmental stage may exacerbate stress to an individual and their family. 3 Understanding outcomes among youth with SCI can help identify areas for attention and improvement.…”
mentioning
confidence: 99%